Global, Regional, and National Burden of Myocarditis From 1990 to 2017: A Systematic Analysis Based on the Global Burden of Disease Study 2017 - Wang, Xiqiang; Bu, Xiang; Wei, Linyan; Liu, Jing; Yang, Dandan; Mann, Douglas L.; Ma, Aiqun; Hayashi, Tomohiro (Frontiers in Cardiovascular Medicine, 2021)
Objective: The global trends in myocarditis burden over the past two decades remain poorly understood and might be increasing during the coronavirus disease 2019 (COVID-19) worldwide pandemic. This study aimed to provide comprehensive estimates of the incidence, mortality, and disability-adjusted life-years (DALY) for myocarditis globally from 1990 to 2017. Methods: Data regarding incidence, mortality, DALY and estimated annual percentage changes (EAPC) between 1990 and 2017 for myocarditis worldwide were collected and calculated from the 2017 Global Burden of Disease study, and we additionally calculated the myocarditis burden distribution base on the social-development index (SDI) quintile. Results: The incidence cases of myocarditis in 2017 was 3,071,000, with a 59.6% increase from 1990, while the age-standardized incidence rate (ASIR) was slightly decreased. The number of deaths due to myocarditis increased gradually from 27,120 in 1990 to 46,490 in 2017. On the contrary, the global age-standardized death rate (ASDR) decreased with an overall EAPC of -1.4 (95% UI=-1.8 to -1.0). The middle SDI quintile showed the highest number of myocarditis-related deaths. There was a 12.1% increase in the number of DALYs in the past 28 years; the middle SDI and low-middle SDI quintiles contributed the most to the DALY number in 2017. Similar to ASDR, the global age-standardized DALY rate also declined, with an EAPC of -1.50 (95% UI=-2.30 to -0.8) from 1990 to 2017. Conclusions: Globally, the ASIR, ASDR, and age-standardized DALY rate of myocarditis decreased slightly from 1990 to 2017. The middle SDI quintile had the highest level of ASIR, ASDR, and age-standardized DALY rate, indicating that targeted control should be developed to reduce the myocarditis burden especially based on the regional socioeconomic status. Our findings also provide a platform for further investigation into the myocarditis burden in the era of COVID-19.